Effects of CO2-induced ocean acidification on the early development, growth, survival and skeletogenesis of the estuarine-dependant sciaenid Argyrosomus japonicus - Erasmus, Bernard (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2018)
Although it is increasingly accepted that ocean acidification poses a considerable threat to marine organisms, little is known about the likely response of fishes to this phenomenon. While initial research concluded that adult fishes may be tolerant to changes predicted in the next 300 years, the response of early life stages to end-of-century CO2 levels (~ 1100 µatm according to the IPCC RCP 8.5) remains unclear. To date, literature on the early growth and survival of fishes has yielded conflicting results, suggesting that vulnerability may be species dependant. The paucity of ocean acidification research on fishes is particularly evident when one considers larval skeletogenesis, with no robust studies on its impacts on bone and cartilage development. This study addresses the early life embryogenesis, hatching success, growth, skeletogenesis and survival of an estuarine-dependant species. Dusky kob (Argyrosomus japonicus) were reared in a control (pCO2 = 327.50 ± 80.07 qatm at pH 8.15), intermediate (pCO2 477.40 ± 59.46 qatm at pH 8.03) and high pCO2 treatment (pCO2 910.20 ± 136.45 qatm at pH 7.78) from egg to 29 days post-hatch (dph). Sixty individuals from each treatment were sacrificed at the egg stage and at 2, 6, 13, 18, 21 and 26 dph, measured and stained using an acid-free double- staining solution to prevent the deterioration of calcified matrices in fragile larval skeletons. The proportion of bone and cartilage was quantified at each stage using a novel pixel-counting method. Growth and skeletal development were identical between treatments until the onset of metamorphosis (21 dph). However, from the metamorphosis stage, the growth and skeletal development rate was significantly faster in the intermediate treatment and significantly slower in the high treatment when compared to the control treatment. By 26 dph, A. japonicus reared in high pCO2 were, on average, 47.2% smaller than the control treatment, and the relative proportion of bone in the body was 45.3% lower in the high pCO2 treatment when compared with the control. In addition, none of the fish in the high pCO2 treatment survived after 26 dph. It appears that the combination of the increased energy requirements during metamorphosis and the increased energy cost associated with acid-base regulation may account for reduced growth, skeletogenesis and poor survival in high pCO2. Regardless of the driver, the results of this study suggest that the pCO2 levels predicted for the end of the century may have negative effects on the growth, skeletal development, and survival during metamorphosis.
Keywords: Argyrosomus; Argyrosomus -- Growth; Argyrosomus -- Mortality; Argyrosomus -- Ecology; Argyrosomus -- Physiology; Ocean acidification; Marine ecology -- South Africa; Carbon dioxide -- Physiological effect